Perampanel for treatment of status epilepticus in Austria, Finland, Germany, and Spain. (20th January 2019) - Strzelczyk, Adam; Knake, Susanne; Kälviäinen, Reetta; Santamarina, Estevo; Toledo, Manuel; Willig, Sophia; Rohracher, Alexandra; Trinka, Eugen; Rosenow, Felix
Abstract : Objective: Novel treatments are needed to control treatment‐resistant status epilepticus (SE). We report a summary of clinical cases where perampanel was used in established SE, refractory SE (RSE), or super‐refractory SE (SRSE). Methods: Medical records were retrospectively reviewed for perampanel administration in SE at five European hospitals between 2011 and 2015. Results: Of 1319 patients identified as experiencing SE, 52 (3.9%) received perampanel. Median latency from SE onset to perampanel initiation was 10 days. Patients with SE had previously failed benzodiazepines (when received) and a median of five other antiepileptic drugs (AEDs). Median initial perampanel dose was 6 mg/d, up‐titrated to a median maximum dose of 10 mg/d. Perampanel was the last drug added in 32/52 (61.5%) patients, with response attributed to perampanel in 19/52 (36.5%) patients. A greater proportion of perampanel non‐responders had SRSE (51.5%; 17/33) vs perampanel responders (31.6%; 6/19), and had failed a higher mean number of AEDs before initiating perampanel (5.9 vs 5.1, respectively). Most commonly reported adverse effects during perampanel treatment were dizziness (n = 1 [1.9%]) and somnolence (n = 1 [1.9%]). No serious adverse effects were documented, and none led to discontinuation of perampanel. Conclusions: Perampanel was administered to patients with established SE, RSE, or SRSE at greater initial doses than those administered in clinical practice to patients with epilepsy. The SE cases reported here represent a refractory and heterogeneous population, and rate of seizure cessation attributed to perampanel treatment (36.5%) represents a notable response. These data should be confirmed in a larger patient population.